The Role of Perceived Enjoyment as a Mediating Influence of Perceived Usefulness and Perceived Ease of Use on Online Shopping Intention (Survey on prospective buyers through E-commerce Shopee in DIY)opping Intention (Survey on prospective buyers through E-commerce Shopee in DIY) - Ayu Frita; Widhy Tri Astuti; Heru Tri Sutiono (LPPM Universitas Buddhi Dharma, 2024)
This research uses explanatory with survey method. The purpose of this study is to test the hypothesis. This study examines the role of perceived enjoyment as a mediating influence of perceived usefulness and perceived ease of use on online shopping intention (Survey of prospective buyers through E-commerce Shopee in DIY). The population in this study are all prospective buyers who have the intention of buying products online through Shopee e-commerce in the Yogyakarta area. The sample in this study used non-probability purposive sampling. The number of samples used in this study were 140 respondents. This study shows the results that directly perceived usefulness has no effect on online shopping intention; perceived ease of use and perceived enjoyment have a significant and positive effect on online shopping intention; perceived usefulness and ease of use have a significant and positive effect on perceived enjoyment. Indirectly perceived usefulness and perceived ease of use have a significant and positive effect on online shopping intention. The limitations of this study are that the object of research focuses on respondents in the Yogyakarta area and it is possible that the results will be different in other research areas. In addition, the limitations of this study only focus on online purchase intention and do not compare with offline purchase intention.